Gastronomic Tourism Travel Routes Based On Android Applications In Ternate City - Turgarini, Dewi; Pridia, Heni; Soemantri, Lioe Lyly (Gastronomy Tourism Journal, 2021)
The rapid development of information technology systems in the world has forced Indonesia to immediately improve its gastronomic tourism information technology system that is easily accessible by tourists. The city of Ternate is unique both in terms of traditional/local food, history, tradition, philosophy, way of eating, way of serving, and educational value. In addition, the city also provide experiences by enjoying nutritious dishes and having good ethics. The method used is descriptive qualitative, through depth interviews, surveys and FGD analysis of the gastronomic component in Ternate City. After that, the second stage was carried out, namely designing an information system in the form of an Android application. This application provides a variety of attractions, accessibility, amenities, and additional services with a menu display that is easy for tourists to use when visiting gastronomic tourist destinations in Ternate City, then spatial mapping is carried out by tagging coordinates so that travel routes can be made. The result of the research is that valid data regarding gastronomic potential data is obtained, and an Android application is made, then an alternative gastronomic travel route is given which is expected to make it easier for special interest tourists to enjoy gastronomic tourist destinations in the city of Ternate. Further research needs to be done in the future so that tourists can extend their stay while enjoying their gastronomic trip in Ternate City.